What Really Explains ESG Performance? Disentangling the Asymmetrical Drivers of the Triple Bottom Line. (March 2023) - Crace, Logan; Gehman, Joel
Why is there such great heterogeneity in environmental, social, and governance (ESG) performance between firms? Drawing inspiration from the locus of performance literature, we use variance partitioning methods to analyze the extent to which CEO, firm, industry, year, and state effects explain variation in ESG performance over recent decades. Our findings show that internal effects (i.e., CEO and firm) are the strongest determinants. Yet, disaggregation of the multidimensional ESG construct shifts the salience of the factors significantly, revealing the importance of the external environment (i.e., industry and year) in explaining ESG concerns. Our research extends the locus of performance literature to our understanding of the triple bottom line and contributes to understanding the complex determinants of firm-level ESG performance across an array of positive and negative ESG indicators.